Organophosphorus flame retardants in mangrove sediments from the Pearl River Estuary, South China. (August 2017) - Hu, Yong-Xia; Sun, Yu-Xin; Li, Xiao; Xu, Wei-Hai; Zhang, Ying; Luo, Xiao-Jun; Dai, Shou-Hui; Xu, Xiang-Rong; Mai, Bi-Xian
Abstract: Forty-eight surface sediments were collected from three mangrove wetlands in the Pearl River Estuary (PRE) of South China to investigate the distribution of organophosphorus flame retardants (OPFRs) and the relationship between OPFRs and microbial community structure determined by phospholipid fatty acid. Concentrations of ΣOPFRs in mangrove sediments of the PRE ranged from 13.2 to 377.1 ng g −1 dry weight. Levels of ΣOPFRs in mangrove sediments from Shenzhen and Guangzhou were significantly higher than those from Zhuhai, indicating that OPFRs were linked to industrialization and urbanization. Tris(chloropropyl)phosphate was the predominant profile of OPFRs in mangrove sediments from Shenzhen (38.9%) and Guangzhou (35.0%), while the composition profile of OPFRs in mangrove sediments from Zhuhai was dominated by tris(2-chloroethyl) phosphate (25.5%). The mass inventories of OPFRs in the mangrove sediments of Guangzhou, Zhuhai and Shenzhen were 439.5, 133.5 and 662.3 ng cm −2, respectively. Redundancy analysis revealed that OPFRs induced a shift in the structure of mangrove sediment microbial community and the variations were significantly correlated with tris(1, 3-dichloro-2-propyl)phosphate and tris(2-butoxyethyl) phosphate. Highlights: OPFRs and microbial community structure were determined in mangrove sediments. OPFRs were linked to the industrialization and urbanization. Distinct distribution patterns of OPFRs were found in the three mangrove wetlands. Eleven OPFRs in the sediments were significantly correlated with the PLFA profiles.